Chemical composition and methane potential of commercial food wastes. (October 2016) - Lopez, Victoria M.; De la Cruz, Florentino B.; Barlaz, Morton A.
Highlights: The methane potential of food waste from four commercial generators was measured. Average methane yields ranged from 363 to 492 mL/dry gm. Lipids and protein dominated the methane potential of food waste. Starch was the compound that exhibited the greatest biodegradation. Abstract: There is increasing interest in anaerobic digestion in the U.S. However, there is little information on the characterization of commercial food waste sources as well as the effect of waste particle size on methane yield. The objective of this research was to characterize four commercial food waste sources: (1) university dining hall waste, (2) waste resulting from prepared foods and leftover produce at a grocery store, (3) food waste from a hotel and convention center, and (4) food preparation waste from a restaurant. Each sample was tested in triplicate 8 L batch anaerobic digesters after shredding and after shredding plus grinding. Average methane yields for the university dining, grocery store, hotel, and restaurant wastes were 363, 427, 492, and 403 mL/dry g, respectively. Starch exhibited the most complete consumption and particle size did not significantly affect methane yields for any of the tested substrates. Lipids represented 59–70% of the methane potential of the fresh substrates.